2003
DOI: 10.1179/joc.2003.15.6.607
|View full text |Cite
|
Sign up to set email alerts
|

Full Dose Paclitaxel Plus Vinorelbine as Salvage Chemotherapy in Anthracycline-Resistant Advanced Breast Cancer: A Phase II Study

Abstract: This phase II trial studied the efficacy and toxicity of full dose paclitaxel plus vinorelbine, as salvage chemotherapy in patients with metastatic breast cancer resistant to anthracyclines. Patients received vinorelbine (30 mg/m2) followed 1 hour later by full dose paclitaxel (175 mg/m2) every 3 weeks for a maximum of 8 cycles or until disease progression. Because of the heavy pretreatment of the patients, prophylactic granulocyte-colony stimulating factor (5 microg/kg) was administered daily for 5-10 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The schedule variable also interacted with the ratio of docetaxel and vinorelbine, suggesting that the ratio was only important if the clinicians chose to intersperse single drug doses between treatments with the combination of drugs (test 8, Table IV). The results of the tests were similar when additional trials, mainly with paclitaxel substituted for docetaxel, were included in the dataset (57,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Analysis Of Chemotherapy Clinical Trialssupporting
confidence: 52%
“…The schedule variable also interacted with the ratio of docetaxel and vinorelbine, suggesting that the ratio was only important if the clinicians chose to intersperse single drug doses between treatments with the combination of drugs (test 8, Table IV). The results of the tests were similar when additional trials, mainly with paclitaxel substituted for docetaxel, were included in the dataset (57,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Analysis Of Chemotherapy Clinical Trialssupporting
confidence: 52%
“…Polyzos and colleagues conducted a Phase II study of salvage therapy in anthracycline-resistant breast cancer patients using paclitaxel and vinorelbine (Tables 1 and 2). 29 They observed a 33% response rate and 8-month median survival and commented that this indicates a lack of cross-resistance between this chemotherapy combination and anthracyclines. Despite use of SC amifostine and G-CSF, 35% of patients developed grade 3 to 4 neutropenia, although no grade 3 to 4 neuropathy was observed.…”
Section: Recent Research: Amifostine and Chemotherapy Regimensmentioning
confidence: 99%
“…A large number of phase II trials have been performed which have generally shown encouraging activity with an acceptable safety profile (Table 3). Examples include Paclitaxel 30–37 Docetaxel; 3846 Doxorubicin; 4751 Epirubicin 5254 Mitoxantrone; 5557 Pegylated Liposomal Doxorubicin; 14,5861 Gemcitabine; 6273 5-Fluorouracil; 7479 platinum compounds; 8083 and Capecitabine, 8488 which will be separately discussed. Several triplets have also been investigated but increased toxicity should be expected.…”
Section: Introductionmentioning
confidence: 99%